Blood eosinophilia in chronic obstructive pulmonary disease: is there a relation with airway eosinophilia? - Atef W El Rifai; Hussein A.M Hussein (Wolters Kluwer Medknow Publications, 2018)
Background Blood eosinophilia was considered an indicator of sputum eosinophilia in asthmatic patients. Nevertheless, its role in chronic obstructive pulmonary disease (COPD) was not completely examined. Aim The aim was to investigate if peripheral blood eosinophilic cells represent an indicator (marker) of eosinophilia of the airway in stable cases. Patients and methods The trial was held at Al-Azhar University Hospital (Damietta), between October 2015 and March 2017. It included 264 persons with stable COPD. All cases were assessed for demographic features, smoking history, history of exacerbation in the last year, dyspnea, associated comorbidities, quality of life, lung functions, sputum, and peripheral blood eosinophilic cell counts. The included participants were allocated into two sets: group with eosinophilia (n=76) and patients without eosinophilia (n=188). Results There was proportional correlation between eosinophilia of the blood and sputum; and blood eosinophilia can differentiate between cases who had or had no sputum eosinophilia at a cutoff of 2.5%. In addition, eosinophil/lymphocyte ratio and eosinophil/neutrophil ratio were higher in eosinophilic COPD and are associated ELR with eosinophilia of the sputum ENR. Conclusion There is correlation between eosinophils of the peripheral blood and sputum in stable cases. Thus, the count of blood eosinophil may act as a dependable marker for eosinophilic COPD